2005
DOI: 10.2134/agronj2005.0095
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Soybean Fungicide Seed Treatments

Abstract: ing a more informed seed treatment decision before planting. Also, since seed cost and associated technology The effects of fungicide seed treatments on seeding rate, location, fees have made seed cost a greater percentage of opsimulated rainfall at emergence, time of planting, and seed quality erating costs (Lambert and Lowenberg-DeBoer, 2003), were analyzed for soybean [Glycine max (L.) Merr.] in this study. Variation in plant emergence allowed estimation of economically analyses surrounding seeding rate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 8 publications
2
29
1
Order By: Relevance
“…were an important component of the seedling disease complex in both soils. In an earlier field study in Arkansas, metalaxyl alone was the most economical seed treatment (30). Metalaxyl seed treatments have been reported to be beneficial on soybean under a no-tillage system in Wisconsin (14).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…were an important component of the seedling disease complex in both soils. In an earlier field study in Arkansas, metalaxyl alone was the most economical seed treatment (30). Metalaxyl seed treatments have been reported to be beneficial on soybean under a no-tillage system in Wisconsin (14).…”
Section: Discussionmentioning
confidence: 96%
“…Bradley et al (5) reported responses to fungicide seed treatments in 1 year (2004) but did not have differences in stands compared with the nontreated control the previous year (2003). Using 'Archer' and 'Hutcheson' soybean, Poag et al (30) reported that metalaxyl was the most economically effective seed treatment. However, in a subsequent study using 'Pioneer M9490' and 'Hombeck 4924' (HBK4924), metalaxyl was not better than the control, but the broad-spectrum seed treatments were effective (31).…”
mentioning
confidence: 99%
“…Specifically, the use of a combination fungicide plus insecticide seed treatment has provided more consistent yield gains across different SRs (Gaspar et al, 2015a) and dissimilar environments and cultivars (Esker and Conley, 2012;Gaspar et al, 2015b), whereas fungicide-only seed treatments have provided smaller and less-consistent yield responses (Bradley, 2008;Gaspar et al, 2015b;Poag et al, 2005;Schulz and Thelen, 2008).…”
mentioning
confidence: 99%
“…Including technology fees, seed cost is a large expense item in soybean production as illustrated by current soybean production budgets (Flanders et al, 2014). Hence, many producers may save costs by minimizing the seeding rate necessary to establish sufficient plant populations to obtain profit‐maximizing yield (Chen and Wiatrak, 2011; Lee et al, 2008; Norsworthy and Oliver, 2001; Poag et al, 2005; Popp et al, 2010). To assist in this decision, producers obtain information from germination tests.…”
Section: Why Look At Seed Qualitymentioning
confidence: 99%
“…Proper seed handling and storage to maintain SQ (Mbofung et al, 2013) is expected to affect the seed's ability to fend off disease, withstand adverse planting conditions, and improve yields (Mengistu and Heatherly, 2006; Vieira et al, 1994). Nonetheless, seed emergence is difficult to predict (Poag et al, 2005; Popp et al, 2003, 2010) and hence research is ongoing to determine the effects of planting date (Bajaj et al, 2008; Poag et al, 2005), ST (Popp et al, 2010), plant population density (PPD) (Ball et al, 2000, 2001; Walker et al, 2010), and SQ on seed survival and ultimately yield.…”
Section: Why Look At Seed Qualitymentioning
confidence: 99%